Burn Out And Job Satisfaction Is There A Connection - Mohd Zul Husni Che Husain; Muhammad Izuddin Ghazali; Mohamad Samir Sulaiman; Hedayatul Akmal Abu Bakar; Hidayati Abdul Rahman (2024)
Burnout associated with stress has been documented in healthcare professionals including National Anti-Drug Agency (NADA) support staff and is considered as one of the potential hazards occurring among individuals who do “people work”. This study aimed to determine the level of job satisfaction and burnout among NADA support staff in several inpatient and outpatient care centre in Malaysia. Descriptive-correlational method of research was utilized to all (91) support staff in several states in Malaysia. Job Satisfaction Survey (JSS) by Pul E. Spector, and Maslach Burnout Inventory (MBI) by Cristina Maslach were administered to the respondents